Political Marketing and the 2015 UK General Election
XI, 151 p. 3 illus., 1 illus. in color.
Keywords: This book brings together leading scholars to analyze political marketing in the context of the UK 2015 General Election. Election campaigns represent a time of intense marketing, including: the communication of party, party leader and candidate brands; the design and dissemination of key messages and policy proposals; identification of target voters; setting out strategies for the campaign; and translating strategies into specific communication tactics. Each chapter of this book has been specifically commissioned to focus on one of these aspects of the campaign (targeted campaigning, branding, core messages, advertising, media management, online campaigning and the campaign in the marginal seats). The collection offers insights into the most interesting and innovative aspects of the 2015 election campaign, determining how levels parties with differing resource approach elections and with what impacts, as well as what we can learn more broadly about marketing at general elections. The chapters are developed to make the topic accessible to non-scholars and to have real-world relevance.